Digital Spaza-shops and the Digitalisation of SMMEs' in South Africa - Matsietsi, Lisema (Graduate School of Business (GSB), 2023)
The purpose of the study investigates the institution of an exclusive financing model to digitalise South African SMMEs to encompass both the sourcing and the administration of development funds for digitalisation. The SMME 4IR (digitalisation) financing model provides finance for SMMEs digitalisation, especially for e-commerce and operational efficiencies. The need for SMME 4IR financing model is driven by fewer digitalised SMMEs given the increasing share of participation in digital marketplaces. SMMEs' finance is provided for the entire scope of business operations, and there exists no special digitalisation finance. The study employed the convergent parallel mixed methods research (MMR) approach to first, to examine the effect of economic factors on internet usage among the population in South Africa using annual secondary data between 1997 and 2017. The second discovered tech SMMEs in South African business incubators and their potential to digitalise other SMMEs. The last objective developed a model for the digitisation of SMMEs in South Africa. The last two objectives followed a qualitative approach. From the quantitative analysis, the study found long run negative relationship is between SMME and Economy and internet usage while Census/Economy and SMME/ICT Services exhibited long run positive effect on internet usage. The qualitative component explored the digitalisation potential of SMMEs using a sample of Tech SMME, venture capitalist (VC), angel investors, and business incubators' public domain (websites). The study found that tech SMMEs embodied significant potential to digitalise other SMMEs. This potential resides in a network of business incubators with private support, VC firms and angel investors-supported programmes. The SMME 4IR financing model has been proposed to address the need to digitalise SMMEs. This model is a hybrid between a equity-based crowdfunding model, existing tech start-up finance, ICT development funds, alternative (innovative) SME fund generation, and other government initiatives relating to SMMEs and 4IR. Business incubators are suitable to administer funds sourced using the SMME 4IR finance model in partnership with business schools. A partnership has been identified as appropriate to solve the lack of expertise associated with finance designed for SMME digitalisation.